Readiness of The Community-Based Organization in Improving Female Adolescents Iron Folate Status in a Rural Area - Apriningsih Apriningsih; Muhammad Reihan Arianda; Widayani Wahyuningtyas; Feda Anisah Makkiyah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
The iron deficiency anemia status of female adolescents needs attention because of its increasing prevalence and impact on adolescent health today and in the future, as well as the country's socio-economic status. Efforts to reduce cases of anemia in female adolescents need to involve multisectoral organizations, including community-based organizations (CBO). Karang-taruna and Posyandu cadres, as CBOs form in rural areas, have the potential to be involved in collaborative programs to improve the anemia status of female adolescents in rural areas. This study aims to identify CBO's readiness to prevent and control anemia in adolescent girls in Sirnagalih village, Bogor, West Java. This study uses a cross-sectional design with a mixed-method approach. The subjects of this study consisted of key resource persons consisting of a village head, three village officers, a head of Karang-taruna, a health-center staff, 6 Karang-taruna members, and 10 Posyandu cadres. The selection of these subjects is based on their role in the village as key persons who willingly participate. The results showed that most CBO members had less knowledge of female adolescents' anemia prevention programs (43.75%). But have a good attitude (56.25%) and self-efficacy (68.75%). The readiness of CBO at Sirnagalih village was at the first level, meaning that CBO members are not aware of the problem of anemia in young women in rural areas. It is necessary to make intervention efforts to increase the readiness of CBOs before further collaborative efforts are carried out.